Asymmetric sulfenylation of 3-CF3-Oxindoles through organocatalysis with a quinidine derivative. Issue 26 (28th June 2017) - E, Yidan; Yuan, Teng; Yin, Liang; Xu, Youjun
Graphical abstract: Highlights: 3-CF3 -oxindoles were obtained in good yield. Asymmetric sulfenylation of 3-CF3 -oxindole was obtained in 84% yield and with 94% ee. The electro-donating groups of 3-CF3 -oxindoles were well tolerated. The electro-donating groups of sulfenylation reagents were well tolerated. The electro-withdrawing groups of sulfenylation reagents were also well tolerated. Abstract: An asymmetric sulfenylation of 3-CF3 -oxindoles catalyzed by a quinidine derivative was described. 3-CF3 -oxindoles with electro-donating groups led to corresponding products in good yield and with good enantioselectivity while 3-CF3 -oxindoles bearing electro-withdrawing groups were not competent substrates due to its significant decomposition at the optimal reaction conditions. As for the sulfenylation reagents based on thiophenol, both electro-donating groups and electro-withdrawing groups were well tolerated.